Gadget Addiction Countermeasures Through Physical Education - Muhammad Akbar Syafruddin; Agus Sutriawan; Nur Indah Atifah Anwar; Sufitriyono (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
This research is descriptive research that uses the literature study method. The method used is a literature study from various previous research articles. The data sources in this research were taken from Google Scholar, Researchgate, and Elsevier. Gadgets are technological advances in the form of sophisticated equipment from previous technology with more practical applications and functions. On the other hand, if its use is not regulated, it will have negative impacts. Uncontrolled and excessive use of gadgets can cause addiction at an early age and have a negative impact on children's development, such as emotional and behavioral problems, lack of movement which causes health problems, and individualistic views. This research tries to overcome the problem of gadget addiction by implementing appropriate physical education. The findings of this research provide an overview of good character development and the expansion of social values that occur during physical education so that the younger generation is not addicted to gadgets.